Gobal dynamics in galactic triaxial systems - Cincotta, Pablo Miguel (2006)
We present a theoretical analysis of the global dynamics in a triaxial galactic system using a 3D integrable Hamiltonian as a simple representation. We include a thorough discussion on the effect of adding a generic non-integrable perturbation to the global dynamics of the system. We adopt the triaxial Stäckel Hamiltonian as the integrable model and compute its resonance structure in order to understand its global dynamics when a perturbation is introduced. We provide a theoretical discussion about diffusive processes taking place in phase space.